A Variational Approach to the Control of Electrochemical Hydrogen Reactions - Costanza, Vicente (2005)
The optimal control problem for the hydrogen evolution reaction (HER) system is posed for different cost objectives and admissible control strategies. The solution for the set-point-change process is given in analytical terms when the admissible controls are the continuous functions of time, and as an implicit feedback law for the piecewise-continuous case. In both cases the cost functional includes a term related to the electrochemical power spent in the process, which is more involved than the classical quadratic type. The theoretical framework remains into the Calculus of Variations for infinite-horizon problems. The Hamiltonian control formalism is adapted to treat the problem when the final time is bounded.